2012
DOI: 10.1016/j.athoracsur.2011.04.121
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Repair of Common Arterial Trunk With Truncal Valve Surgery: A Review of The Society of Thoracic Surgeons Congenital Heart Surgery Database

Abstract: Background Previous studies have suggested truncal valve insufficiency may adversely affect outcome after common arterial trunk (CAT) repair. It is unknown if truncal insufficiency requiring truncal valve surgery (TVS) at the time of primary CAT repair impacts outcome. Methods Patients in the STS Congenital Heart Surgery Database undergoing CAT repair from 2000–2009 were included. Outcomes were compared for those with and without TVS at the time of CAT repair and were further stratified by interrupted aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 23 publications
3
92
1
3
Order By: Relevance
“…This is in contradistinction to published series of truncal valve repairs and replacements in which long-term survivals have been noted to be compromised. 14 Of the valve replacement options applied to small patients (children in whom adult-sized prostheses cannot be used), the Ross procedure appears to be the most durable. 15,16 Although not always possible owing to anatomic defects and clearly a more technically demanding procedure, several large studies including our own have shown excellent midterm and long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contradistinction to published series of truncal valve repairs and replacements in which long-term survivals have been noted to be compromised. 14 Of the valve replacement options applied to small patients (children in whom adult-sized prostheses cannot be used), the Ross procedure appears to be the most durable. 15,16 Although not always possible owing to anatomic defects and clearly a more technically demanding procedure, several large studies including our own have shown excellent midterm and long-term results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite major improvements in the perioperative care of these patients, reported in-hospital death remains high (9%-11%). 2,3 Although the report of Mastropietro and colleagues 1 shows a slightly lower operative mortality, the limited number of experienced centers that have participated in this study may have influenced this finding. Moreover, despite the somewhat lower operative mortality risk, the study of Mastropietro and colleagues 1 still shows significant postoperative morbidity.…”
Section: Bahaaldin Alsoufi MDmentioning
confidence: 78%
“…Previous studies have demonstrated hospital mortality between 5-19%(5,9,11-14,16,18,19) with the largest series from the Society for Thoracic Surgery Congenital Heart Surgery Database demonstrating an unadjusted mortality of 10%(10,14,20). Our study design does not provide peri-operative mortality data, and we cannot comment on how our cohort compares to those in previous studies in this domain.…”
Section: Discussionmentioning
confidence: 99%